PREVENTION AND CONFLICT RESOLUTION AT JUNIOR SCHOOL AGE - Каchmar Oleksandra; Krytsak, Oksana (Mountain School of Ukrainian Carpaty, 2018)
The problem of conflict is extremely relevant, in recent years the theory and practice of conflict resolution are developing rather quickly. The purpose of the paper is to clarify the concept of conflict, the factors that affect the emergence of conflict situations among pupils of junior school age, the definition of ways to correct behavior to overcome conflicts. The task of the study is to identify the psychological features of the conflict, factors contributing to their occurrence, to consider the types of school conflicts, the main factors and causes of conflict situations in junior pupils. The author used the following methods of research: systematization and generalization of philosophical, psychological and pedagogical, scientific and methodological literature on the problem of conflict resolution, empirical methods: generalization, comparison. The process of forming the child's personality takes place at school. The number of conflicts between schoolchildren increases or decreases depending on how successful this process is. An important role in preventing conflicts is played by discipline which is the ability to provide a child necessary for his development freedom within the framework of reasonable subordination in the established order. The aim of our work is to study the causes of conflicts and consider the most effective ways of solving hem. The reorganization of the modern system of pedagogical activity in terms of ensuring the versatile and balanced development of the individual requires a special teacher's attention to the student at the critical stages of his mental and social development. Confrontation with children, unfavorable living conditions have become commonplace, so the conflict permanently takes place in the school environment. The authors review the types of school conflict and the ways of their prevention in the educational environment.